Bank risk-taking and impaired monetarypolicy transmission - Philipp J. Koenig; Eva Schliephake (Deutsche Bundesbank, 2021)
We consider a standard banking model with agency frictions to simultaneously studythe weakening and reversal of monetary transmission and banks' risk-taking in alow-interest environment. Both, weaker monetary transmission and higher risk-taking arise because lower policy rates impair banks' net worth. The pass-throughto deposit rates, the level of excess reserves and the extent of the agency problembetween banks and depositors are crucial determinants of monetary transmission.If the deposit pass-through is sufficiently impaired, a reversal rate exists. For policyrates below the reversal rate further interest rate reductions lead to a disproportionalincrease in risk-taking and a contraction in loan supply.
Keywords: G21; E44; E52; 330; Monetary policy; Bank lending; Risk-taking channel; Reversal rate